Deliberation, Polarization, and Emotion: A Deliberative Process about Climate Change with Young Participants - Brasileiro, Juliana Montenegro [UNESP]; García-Leiva, Patricia; Palacios-Gálvez, M. Soledad; González, Marta Barros (Springer Nature, 2025)
In light of the increase in democratic innovation processes in recent decades, there is ongoing debate as to whether deliberative participation reduces levels of affective and issue-based political polarisation. This field study analyses the role of emotions in a deliberative process about climate change conducted by the AOS! Programme in Spain in 2022. 137 participants aged 10–12 years organised into mixed and enclave groups answered a survey to determine their level of concern about climate change and both affective and issue-based polarisation, in order to assess whether feeling worried about climate change could influence their level of political polarisation. The results show that neither the enclave nor the mixed groups had significant effects on their affective polarisation, as the children only answered according to their level of concern about climate change. However, participation influenced their levels of issue-based polarisation, depolarising less worried participants. These findings demonstrate that emotions have an impact on cognition through participation and that feelings about political topics should be considered in deliberative studies.
Keywords: Child participation; Climate change; Deliberation; Political polarisation